Erythromycin effect on the intestinal microbial community of rats - E.V. Skvortsov; Rish.S. Muhammadiev; Rin.S. Muhammadiev; L.R. Valiullin (Учёные записки Казанского университета: Серия Естественные науки)
The effect of erythromycin on the intestinal microbial community of laboratory rats was studied. The research is important for the practical purposes of animal farming and veterinary medicine, because a significant increase in the abundance of pathogenic microorganisms caused by antibiotic treatment turns the intestine into a reservoir of infections resistant to antibiotics, which need to be combated efficiently. To solve this problem, both rapid and accurate methods must be elaborated for quantitative determination of the main bacteria in the intestine during the use of antibiotics, such as erythromycin. We used genetic analysis (real-time polymerase chain reaction) to study the intestinal microflora of male rats aged 8 weeks. All rats were divided into two groups: the control group (n = 10); the experimental group (n = 10) that received orally administered erythromycin. The abundance of the main intestinal bacteria was determined from fecal samples. The content of several variations of erm (erythromycin resistance) genes in the intestinal microflora was also investigated. The obtained results demonstrate that erythromycin causes a significant increase in the abundance of Clostridium difficile and Staphylococcus aureus, as well as in the number of erm genes. These data can be considered a further advance in our understanding of prospects and consequences of antibiotic therapy in animal farming and veterinary medicine.